EFFECT OF ADDITIVES ON VARIOUS SPERMATOZOAL ATTRIBUTES OF FRESH, FROZEN-THAWED AND REFRIGERATED SEMEN - RAVAL, RUPESH J; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
Thirty six ejaculates from 4 mature triple crossbred (25% HF x 25% J x 50% Kankrej) bulls werespli1 into 3 aliquots each and were processed for freezing and refrigeration storage in TFYG diluentwithout and with EDTA(0.1 %) or Cysteine HCI (0,1%). The percentages of motile and live sperm andintact acrosome were significantly (P < 0.01) higher in presence of EDTA and/or cysteine as comparedto control Tris diluent at all steps of semen processing/ preservation. Further, the motile sperms atinitial, prefreeze, post-thaw and post-refrigeration stages were highly significantly (P < 0.01) interrelated(r = 0.35 to 0.88), and so also were the cases for iive sperm (0.26 to 0. 76), abnormal sperm {0.20 to0.62) and intact acrosome (0.30 to 0.76). Moreover, the sperm motility at different steps of semenprocessing/preservation had significant (P
Keywords: Semen additives; Crossbred bulls; Freezability; Interrelationships